Penguatan Pendidikan Karakter Religius Melalui Kondisioning Sholat Dhuha Berjamaah di SMK YPM 12 TUBAN - M.Mahfudz Arif; Nabila Muslim; Khofifah Habibul Ulum (Yayasan Al-Afif, 2026)
This study aims to analyze the strengthening of religious character education through congregational Dhuha prayer activities at SMK YPM 12 Tuban. The study used a descriptive qualitative approach with data collection techniques in the form of in-depth interviews with teachers as key informants. The results of the study indicate that the implementation of congregational Dhuha prayers is carried out in a scheduled and structured manner as part of the student religious habituation program, which is carried out routinely every Tuesday, Thursday, and Friday, and every day during the month of Ramadan. This activity is also integrated with the study of the book as an effort to deepen students' religious understanding. Although legally Dhuha prayer is sunnah, in the school context this activity is institutionally mandatory as a form of character education strategy. Implementation is strictly monitored by teachers through a structured system, and supported by the imposition of light sanctions that are educational in nature for students who do not participate in the activity. The results of the study indicate that the habituation of congregational Dhuha prayers can improve students' discipline, responsibility, and spiritual awareness, while also forming good morals and reducing negative behavior. Thus, this activity serves not only as a form of worship but also as an effective means of internalizing religious values ​​and shaping students' overall character in their daily lives.